1996
DOI: 10.1111/j.1365-2311.1996.tb00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mating frequency and brood cell infestation rate on the reproductive success of the honeybee parasite Varroa jacobsoni

Abstract: . The reproductve biology of Varroa jacobsoni, whose females infest honeybee brood, was studied in natural and transparent artificial brood cells. These investigations were made under the headings of maturation behaviour and fertilization, and the influence of infestation rate of brood cells on the number of mated females produced per infesting Varroa. Mating of Varroa daughters, observed in the transparent brood cells with time‐lapse video, occurs just after ecdysis and as soon as they arrive on the faecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
2
4

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 44 publications
8
80
2
4
Order By: Relevance
“…As brood area started expanding, favouring the entry of Varroa into brood cells as well as their reproduction, its population showed an increasing trend. These results corroborated the earlier studies that large number of sealed brood cells contributed to increase in mite population (Donze et al, 1996).…”
Section: Comparison Of Sampling Methodssupporting
confidence: 93%
“…As brood area started expanding, favouring the entry of Varroa into brood cells as well as their reproduction, its population showed an increasing trend. These results corroborated the earlier studies that large number of sealed brood cells contributed to increase in mite population (Donze et al, 1996).…”
Section: Comparison Of Sampling Methodssupporting
confidence: 93%
“…This relationship between development time of the bee brood and mite mortality had previously been suggested by Baggio (1994) (Martin, unpublished data). Various studies have found that 18% (Boot et al, 1995), 30% (Martin and Kemp, 1997) (Boot et al, 1995;Donzé et al, 1996) to around 0.8-0.9 mites per reproductive cycle in worker cells and from 2-2.2 (Martin, 1995) to 1.9-2.1 in drone cells.…”
Section: Methodsmentioning
confidence: 99%
“…The adult male copulates repeatedly with each of its sisters (adelphogamy). However, two, or more rarely several, foundresses may lay eggs in the same cell (Fuchs & Langenbach 1989;Martin 1995;Donzé et al 1996). In that case, mating may occur between individuals of different lineages.…”
Section: Introductionmentioning
confidence: 99%